2021
DOI: 10.1029/2021gl092744
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID‐19 on CO2 Emissions in the Los Angeles and Washington DC/Baltimore Metropolitan Areas

Abstract: Responses to public health threats presented by the global COVID-19 pandemic dramatically altered daily activities in cities around the world, including in the Los Angeles and Washington DC/Baltimore metropolitan areas. Researchers have attempted to determine the extent to which CO 2 emissions were impacted by the pandemic, linking changes in emissions to processes and sectors using different types of activity data and baselines for comparisons (Le Quéré et al., 2020;Liu et al., 2020;Zheng et al., 2020). One s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 45 publications
2
39
2
Order By: Relevance
“…The CO 2 Urban Synthesis and Analysis (CO 2 -USA) network is a synthesis effort primarily supported by the U.S. National Oceanic and Atmospheric Administration, with additional support from National Institute of Standards and Technology. CO 2 -USA was established to build a collaborative network of urban carbon cycle researchers to facilitate data sharing, create analysis frameworks to enable cross-city synthesis analyses 19 , and enable new collaborations tackling objectives that are difficult to address in isolation (Fig. 1 ).…”
Section: Background and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…The CO 2 Urban Synthesis and Analysis (CO 2 -USA) network is a synthesis effort primarily supported by the U.S. National Oceanic and Atmospheric Administration, with additional support from National Institute of Standards and Technology. CO 2 -USA was established to build a collaborative network of urban carbon cycle researchers to facilitate data sharing, create analysis frameworks to enable cross-city synthesis analyses 19 , and enable new collaborations tackling objectives that are difficult to address in isolation (Fig. 1 ).…”
Section: Background and Summarymentioning
confidence: 99%
“…Building a multi-city analysis framework will enable studies to quantify and understand similarities and differences in how much, where, and why GHG fluxes differ across cities. Applications could include assessing changes in emissions during the COVID-19 pandemic or creating consistent methodologies to assess emissions across different cities that are pursuing emission reduction policies 19 . This information could then be presented to urban stakeholders and policymakers to evaluate progress towards emission reduction goals (Fig.…”
Section: Background and Summarymentioning
confidence: 99%
“… 2 , 3 Atmospheric observations of CO 2ff during COVID-19 lockdowns have not yet been reported, and only a small number of studies have detected changes from atmospheric observations of total CO 2 . 9 12 …”
Section: Introductionmentioning
confidence: 99%
“…Such networks have been deployed for several years at several cities across the globe, have nearreal-time dedicated high-precision, high-accuracy measurements of CO 2 , carbon monoxide (CO), and methane (CH 4 ) [9][10][11][12][13][14][15]. These networks have been used to infer [16] or quantify [17] changes in emissions over time, and with atmospheric inverse systems for the quantification of urban emissions [12], [18][19][20]. Recently, this technique was used to quantify the relative reduction of CO 2 emissions from activities associated with COVID-19 in Los Angeles and D.C./Baltimore, [20] and San Francisco [21].…”
Section: Introductionmentioning
confidence: 99%
“…These networks have been used to infer [16] or quantify [17] changes in emissions over time, and with atmospheric inverse systems for the quantification of urban emissions [12], [18][19][20]. Recently, this technique was used to quantify the relative reduction of CO 2 emissions from activities associated with COVID-19 in Los Angeles and D.C./Baltimore, [20] and San Francisco [21]. Both studies found emissions reductions on the order of 30%.…”
Section: Introductionmentioning
confidence: 99%